SIFAT-SIFAT FUNGSI FIBONACCI PADA BILANGAN FIBONACCI - Samson Manalu; Mashadi '; Rolan Pane (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2015)
For every function ݂: ℝ → ℝ, with f(x  2)  f(x 1)  f(x), for ݔ ∈ ℝ is called the Fibonacci function. In this article, we discuss the properties of a Fibonacci function on Fibonacci Numbers. Among them is the multiplication of an odd function or an even function with a Fibonacci function, also produces a Fibonacci function. If the Fibonacci function f convergens, it convergens to a number 2 1  5 called golden ratio. This implies that limit of a Fibonacci function exists.